Contribution of Sociology Education in Realizing Tolerance and Diversity at SMA Negeri 5 Makassar - Hanafi, Ali; Rudia, Sitti Nasrawati; Saidin, La Ode (International Journal on Advanced Science, Education, and Religion, 2024)
This study aims to determine the contribution of sociology education in forming attitudes of tolerance and accepting diversity among students of SMA Negeri 5 Makassar. Through a descriptive qualitative approach, data were collected through observation, interviews with sociology teachers and students, and learning documentation. The results of the study indicate that sociology education plays a strategic role in shaping students' understanding of the importance of living in diversity, respecting differences, and avoiding social conflict. Sociology materials such as social structure, social interaction, and cultural values ​​are the foundation for building students' social awareness. Thus, sociology education makes a positive contribution to creating a harmonious and inclusive school environment.